Karyomapping allows preimplantation genetic diagnosis of a de-novo deletion undetectable using conventional PGD technology. Issue 6 (December 2015) - Giménez, Carles; Sarasa, Jonás; Arjona, César; Vilamajó, Ester; Martínez-Pasarell, Olga; Wheeler, Kenny; Valls, Gemma; Garcia-Guixé, Elena; Wells, Dagan
Abstract: Preimplantation genetic diagnosis (PGD) was carried out for a couple carrying a de-novo deletion in the TSC2 gene, responsible for tuberous sclerosis. Karyomapping, a method employing genome-wide analysis of single nucleotide polymorphisms (SNP), was used as PGD protocol. Analysis of DNA from the affected parent using karyomapping confirmed the region covered by the deletion and revealed more than 30 SNP located within the affected region. These SNP were subsequently used for embryo diagnosis (deletion revealed by hemizygosity and/or reduced probe intensity). Seven blastocyst embryos underwent trophectoderm biopsy followed by vitrification. Biopsied cells were subjected to comprehensive aneuploidy screening using microarray comparative genomic hybridization (aCGH), with karyomapping for the detection of embryos carrying the mutant TSC2 gene carried out in tandem. Two embryo transfers were performed, the second of which resulted in the birth of a child. This study highlights that karyomapping may be applicable to a subset of de-novo mutations undetectable using standard PGD strategies. Additionally, karyomapping results were in complete concordance with aCGH, both methods revealing the same aneuploidies in the embryos tested. It was concluded that karyomapping may represent a valuable advance in cases of PGD for monogenic diseases.